# The sum of three terms which are in arithmetic progression$A.P$ is $33$ , if the product of the ${1^{st}}$ and ${3^{rd}}$ terms exceeds the ${2^{nd}}$ term by 29, find $A.P$ .

Answer

Verified

361.8k+ views

Hint: In order to solve these type of question, firstly we have to find out the $a$ and difference between two consequent terms $d$ and assuming the first three terms of $A.P$ is $\left( {a - d} \right),a,\left( {a + d} \right)$.

Complete step-by-step answer:

Assuming , second term $ = a$ ,common difference$ = d$

Given, That the sum of three terms is $33.$

Now,

$\left( {a - d} \right) + a + \left( {a + d} \right) = 33$

Now, opening the brackets.

Or $a - d + a + a + d = 33$

Or $3a = 33$

$a = 11 - - - - - - \left( 1 \right)$

Now, according to the given question if the product of the ${1^{st}}$ and ${3^{rd}}$ terms exceeds the ${2^{nd}}$ term by 29.

So, we have to add $29$ on $R.H.S$ or in $a$ to balance the equation .

$\left( {a - d} \right) \times \left( {a + d} \right) = a + 29$

Or ${a^2} - {d^2} = a + 29$

Substituting the value of $a$ from(1) we get

Or ${11^2} - {d^2} = 11 + 29$

Or $121 - 40 = {d^2}$

Or ${d^2} = 81$

$d = \pm 9 - - - - - \left( 2 \right)$

Due to two different values of $d$ there are two cases for arithmetic progression.

Case 1,

If $a = 11,d = 9$

$\left( {a + d} \right) = 11 + 9 = 20$

$\left( {a - d} \right) = 11 - 9 = 2$

Therefore, arithmetic progression is $2,11,20,29,38........$

Case 2,

If $a = 11,b = - 9$

$\left( {a + d} \right) = 11 + \left( { - 9} \right) = 2$

$\left( {a - d} \right) = 11 - \left( { - 9} \right) = 20$

Therefore arithmetic progression is $20,11,2, - 7, - 16..........$

Note: Whenever we face these type of question the key concept is that we know that the arithmetic progression series $\left( {a - d} \right),a,\left( {a + d} \right)$ then we have to find out the common difference of two terms using $a$ and after getting both $a$ and $d$ put their value in $A.P$ and we will get our desired answer.

Complete step-by-step answer:

Assuming , second term $ = a$ ,common difference$ = d$

Given, That the sum of three terms is $33.$

Now,

$\left( {a - d} \right) + a + \left( {a + d} \right) = 33$

Now, opening the brackets.

Or $a - d + a + a + d = 33$

Or $3a = 33$

$a = 11 - - - - - - \left( 1 \right)$

Now, according to the given question if the product of the ${1^{st}}$ and ${3^{rd}}$ terms exceeds the ${2^{nd}}$ term by 29.

So, we have to add $29$ on $R.H.S$ or in $a$ to balance the equation .

$\left( {a - d} \right) \times \left( {a + d} \right) = a + 29$

Or ${a^2} - {d^2} = a + 29$

Substituting the value of $a$ from(1) we get

Or ${11^2} - {d^2} = 11 + 29$

Or $121 - 40 = {d^2}$

Or ${d^2} = 81$

$d = \pm 9 - - - - - \left( 2 \right)$

Due to two different values of $d$ there are two cases for arithmetic progression.

Case 1,

If $a = 11,d = 9$

$\left( {a + d} \right) = 11 + 9 = 20$

$\left( {a - d} \right) = 11 - 9 = 2$

Therefore, arithmetic progression is $2,11,20,29,38........$

Case 2,

If $a = 11,b = - 9$

$\left( {a + d} \right) = 11 + \left( { - 9} \right) = 2$

$\left( {a - d} \right) = 11 - \left( { - 9} \right) = 20$

Therefore arithmetic progression is $20,11,2, - 7, - 16..........$

Note: Whenever we face these type of question the key concept is that we know that the arithmetic progression series $\left( {a - d} \right),a,\left( {a + d} \right)$ then we have to find out the common difference of two terms using $a$ and after getting both $a$ and $d$ put their value in $A.P$ and we will get our desired answer.

Last updated date: 23rd Sep 2023

â€¢

Total views: 361.8k

â€¢

Views today: 9.61k